EXPLORATION OF THE USE OF DIGITAL STORYTELLING IN SOCIAL STUDIES LEARNING: A BIBLIOMETRIC ANALYSIS STUDY - Muhammad Rijal Fadli; Imam Santosa; Khusnul Fatonah; Harlinda Syofyan; Vjollca Jonuzi (Jurnal Eduscience, 2025)
Purpose – Digital storytelling as a form of technology integration in education has provided a new way of learning Social Studies in elementary schools. Although its effectiveness has been proven in various disciplines, the literature discussing the specific use of digital storytelling in elementary school social studies is still minimal. This study aims to fill this gap by exploring publication patterns, research trends, and collaborations related to the use of digital storytelling in elementary school social studies learning.